Mortality of Urban Aboriginal Adults in Canada, 1991–2001 - Tjepkema, Michael (Centers for Disease Control and Prevention, 2010)

(untitled)
OBJECTIVE: To compare mortality patterns for urban Aboriginal adults with those of urban non-Aboriginal adults. METHODS: Using the 1991–2001 Canadian census mortality follow-up study, our study tracked mortality to December 31, 2001, among a 15% sample of adults, including 16 300 Aboriginal and 2 062 700 non-Aboriginal persons residing in urban areas on June 4, 1991. The Aboriginal population was defined by ethnic origin (ancestry), Registered Indian status and/or membership in an Indian band or First Nation, since the 1991 census did not collect information on Aboriginal identity. RESULTS: Compared to urban non-Aboriginal men and women, remaining life expectancy at age 25 years was 4.7 years and 6.5 years shorter for urban Aboriginal men and women, respectively. Mortality rate ratios for urban Aboriginal men and women were particularly elevated for alcohol-related deaths, motor vehicle accidents and infectious diseases, including HIV/AIDS. For most causes of death, urban Aboriginal adults had higher mortality rates compared to other urban residents. Socio-economic status played an important role in explaining these disparities. CONCLUSION: Results from this study help fill a data gap on mortality information of urban Aboriginal people of Canada. KEYWORDS: Aboriginal people, First Nations, Métis, Inuit, North American Indians, age-standardized mortality rates, mortality rate, life expectancy